Systemic onset juvenile idiopathic arthritis: a single center experience - Sağ, Erdal; Uzunoğlu, Berna; Bal, Fatma; Sönmez, Hafize Emine; Demir, Selcan; Bilginer, Yelda; Özen, Seza (The Turkish Journal of Pediatrics, 2019)
Systemic juvenile idiopathic arthritis (sJIA) presents with prolonged fever and systemic features such as arthritis, rash, lymphadenopathy, hepatosplenomegaly and serositis. In this study, we aimed to evaluate the clinical and laboratory findings, and outcomes of sJIA patients from a tertiary rheumatology center. Between 2010-2017, patients who had been diagnosed with sJIA, participated in the study. The demographics, clinical and laboratory features, and outcomes, were evaluated retrospectively. Seventy-five sJIA (%56 male) patients were enrolled. The mean age at diagnosis was 6,45±4,80 years. At the time of diagnosis, the most common findings were fever (%100) followed by arthritis (78,7%), and rash (66,2%). Twenty-four percent of the patients present with macrophage activation syndrome (MAS) at the time of diagnosis. Totally, 36% of the patients had at least one MAS attack during the course of the disease. 46% of the patients had polyphasic course while 54% had one attack (26% monophasic, 28% persistant). All of the patients were treated with non-steroid anti-inflammatory drugs (NSAID) and/or corticosteroids at the beginning of the disease. Twenty percent of the patients reached remission with corticosteroid or disease-modifying anti-rheumatic drugs (DMARDs) however the rest of the patients needed at least one biologic agent. Anakinra was the most common first-line biologic treatment choice (n=45). Fourteen (18,7%) of the patients had polyarticular joint involvement during the disease course, and 5 of them achieved remission with tocilizumab. Systemic JIA is an important disease with high risk of morbidity and mortality. As our center is one of the most important tertiary referral rheumatology centers in the country, we had a high MAS incidence. Eighty percent of the patients achieved remission with a biological agent. Anti-IL1 drugs are mostly preferred for ongoing systemic inflammation. Anti-IL-6 agents are very efficient in patients with a polyarticular course.
Keywords: MAS; macrophage activation syndrome; sJIA; sJIA treatment; systemic juvenile idiopathic arthritis